ASSESSMENT OF THE RISK OF DEVELOPING DIABETES MELLITUS IN MEN WITH DIFFERENT LEVELS OF CARDIOVASCULAR RISK (The Conference Hub, 2025)
At the beginning of the third millennium, the problem of cardiovascular diseases (CVD) came to the forefront in terms of relevance among all causes of morbidity and mortality. According to forecasts of the World Health Organization (WHO), by 2030 about 23.6 million people will die from CVD, mainly from heart disease and stroke, which are the main causes of death among people of working age. Heart disease, like many other chronic non-communicable diseases, develops slowly and "unnoticed". In the structure of mortality of the adult population, the share of complications of CVD (ischemic heart disease (IHD) and stroke) today is 40-60%. There is a tendency for these diseases to "rejuvenate" - there are frequent cases when myocardial infarction (MI) is observed in 2-5-year-old people, which is the most important medical and social problem. One of the important reasons for the increase in the prevalence of CVD is the presence of a number of concomitant diseases. In particular, an increased risk of developing coronary heart disease is associated with the presence of metabolic disorders and diabetes mellitus (DM) in patients. Modern studies have established common mechanisms of the pathological process of DM and CVD formation, which allows us to consider DM as an endocrinological equivalent of coronary heart disease. Interest in early disorders of carbohydrate metabolism has increased significantly in recent years. Prediabetes is an intermediate stage between normal glucose tolerance and type 2 DM. The annual conversion of impaired glucose tolerance (IGT) to type 2 DM, according to prospective studies, is 4-8%. The development of algorithms and accessible tools for identifying the risk of developing DM in individuals with cardiovascular risk is an urgent problem in modern cardiology.